Intraosseous adenoid cystic carcinoma of the mandible: A rare presentation - Indu, Sudip (J Oral Maxillofac Pathol, 2020)
Central adenoid cystic carcinoma (ACC) of the mandible is a rare entity arising from minor salivary glands. Their clinical and radiographic features may be similar to any odontogenic/nonodontogenic pathology, thus making their precise diagnosis wearisome. ACC is well documented for its protracted clinical course, perineural invasion, multiple recurrence rates and its propensity for distant metastases. The aim of this study is to report a rare case of primary central ACC of the mandible with an unusual presentation in terms of location, however, demonstrating the classical features of ACC in histopathology and positivity in immunohistochemistry to S100, calponin and CD117. A thorough clinical, radiographic, CT evaluation and meticulous metastatic workup along with long-term follow-up is advised in such cases. Although central ACC is extremely rare, especially in the anterior mandible, it should be included in the differentials for lesions of the mandible.